Cultivation practices and performance indicators of vannamei shrimp in HDPE-lined ponds at Prigi Mariculture Installation, Trenggalek, Indonesia - Andaya, Fity; Halim, Abdul; Purnama, Candra Eka Hari (Journal of Marine Resources and Coastal Management, 2024)
The development of fisheries potential can be enhanced through various cultivation activities, with shrimp farming being one of the key sectors. This study evaluates the cultivation of vannamei shrimp (Litopenaeus vannamei) in High-Density Polyethylene/HDPE-lined ponds at the Prigi Mariculture Installation, Trenggalek, focusing on pond preparation, media setup, shrimp maintenance, water quality management, and their impact on key performance indicators: survival rate (SR), feed conversion ratio (FCR), average body weight (ABW), and average daily growth (ADG). The study was conducted in four ponds: B1 and B2 (1,350 m³) and B3 and B4 (1,000 m³), stocked with post-larvae at densities of 118-122 individuals/m³. Water quality measurements included 29°C temperature, 15-24 ppt salinity, 6.8-7.7 pH, 7.02–7.78 mg/L dissolved oxygen, and 32-100 cm brightness. Growth rates varied, with the highest ADG at 0.30 and the lowest at 0.0. FCR values ranged from 1.64 (B3) to 1.84 (B4), while SR ranged from 26% to 51%. The presence of pests, such as birds, monitor lizards, and mice, and diseases like Acute Hepatopancreatic Necrosis Disease (AHPND) and White Feces Disease (WFD), were noted. These findings provide valuable insights into optimizing vannamei shrimp farming practices and improving productivity in HDPE-lined ponds.